Tin powder‐promoted oxidation/allylation of glycine esters: Synthesis of γ, δ‐unsaturated α‐amino acid esters. (18th October 2021) - Zhao, Pengfei; Huang, Danfeng; Wang, Feng; Han, Tongyu; Yang, Ming; Wang, Ke‐Hu; Hu, Yulai
Abstract : An efficient tin powder‐promoted oxidation/allylation reaction of glycine esters with allyl bromides is developed, which affords γ, δ ‐unsaturated α ‐amino acid esters under mild conditions without any other transition metal catalysts. This method avoids the use of unstable imine as starting material, and provides an efficient method for synthesis of γ, δ ‐unsaturated α ‐amino acid esters and α ‐methylene‐ γ ‐lactam derivatives. Additional supporting information may be found in the online version of this article at the publisher's web site. Abstract : An efficient tin powder‐promoted oxidation/allylation reaction of glycine esters with allyl bromides is developed, which affords γ, δ ‐unsaturated α ‐amino acid esters under mild conditions without any other transition metal catalysts. This method avoids the use of unstable imine as starting material and provides an efficient method for synthesis of γ, δ ‐unsaturated α ‐amino acid esters and α ‐methylene‐ γ ‐lactam derivatives.